Tactic of banishment as a structural component of vindictive discourse (direct and indirect forms of presentation) - Chesnokov, I. I. (Cognition, Communication, Discourse, 2018)
Mental epicentre, motive, aim, strategies and tactics of vindictive discourse are described in this article. Direct and indirect forms, presenting tactic of banishment as a structural component of mentioned above type of speech activity, get enlightment. Communicative-semantic field of forms, which present this tactic, is constructed.